(untitled) (Numerus academy review, 2026)
This study deals with the relationship between general international law and national law in the light of international practice and Algerian legislation, as this topic raises many legal questions related mainly to the hierarchy of legal rules, given the overlap of legal rules. legal relations and the participation of international law in national legislation in matters which are the basis of the competence of internal law, just as international law prevails over national law, or is national law superior to international law, and several theories have emerged to assert which laws are superior to each other through two doctrines. The first relates to dualist theory, and the other tends The theory of unity of law, however, that it is in fact constitutions that clarify the place of international law in the legal system of the state. We will try to demonstrate the practical application of trends in international justice and the Vienna Convention of Treaties, as well as Algerian law to determine the superiority of Public international law over the National law.